Oblique Lumbar Interbody Fusion for Lumbar Degenerative Adjacent Segment Disease: A Single-center Case Series - Chung-Tse Chang; Yu-Hsien Lin; Yun-Che Wu; Cheng-Min Shih; Kun-Hui Chen; Chien-Chou Pan; Cheng-Hung Lee (Formosan Journal of Musculoskeletal Disorders)
Background: In the past decade, oblique lumbar interbody fusion (OLIF) has gradually become popular for degenerative lumbar disc disease; however, studies reporting the outcomes of OLIF for the treatment of adjacent segment disease (ASD) are scarce. Objectives: The objective is to investigate the short-term clinical and radiographic outcomes of OLIF for lumbar ASD and analyze its advantages and disadvantages compared to other surgical methods. Materials and Methods: Twenty-six patients who received previous lumbar fusion surgery underwent second lumbar surgery for ASD; all were treated with OLIF and posterior instrumentation. Posterior decompression was added for 16 patients. Clinical outcomes, including quality-adjusted life years, Oswestry Disability Index, Visual Analog Scale for back and leg pain, and radiologic parameters, including disc height (DH), foraminal height, segmental lordosis, and lumbar lordosis, were evaluated preoperatively, postoperatively, at 3 and 6 months postoperatively, and last follow-up. Results: All clinical functional outcomes and radiologic outcomes significantly improved for all patients after OLIF surgery (P < 0.05). OLIF without posterior decompression had a significantly shorter operating time (341 vs. 420 min; P = 0.007) and less blood loss (150 vs. 475 cc; P = 0.001) than OLIF with posterior decompression. One case had an intraoperative dural tear; no cases had major vascular or nerve injury, postoperative cage subsidence, migration, or nonunion. Conclusions: OLIF surgery for lumbar ASD has good clinical results and improves radiologic parameters, such as DH restoration and sagittal alignment correction. Posterior instrumentation is suggested for concerns related to spine stability. Posterior decompression may be necessary for severe spinal canal stenosis, locked facet joint, and noncontained disc herniation.